Mobile Apps for Allergies: A Systematic Review and Quality Assessment Using the Mobile Application Rating Scale (MARS) - Olszar, Agata; Książek, Ewelina; Konikowska, Klaudia (Aplikacje mobilne dotyczące alergii: przegląd systematyczny i ocena jakości za pomocą skali MARS (Mobile Application Rating Scale), 2024)
Aim: With the growing reliance on mobile apps by individuals with allergies and food intolerances, this study aimed to evaluate their quality and usability. Using the Mobile Application Rating Scale (MARS), we assessed allergy-related apps available on Google Play and the AppStore. Methodology: Using the PRISMA elimination method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), three apps were selected from the available options: Soosee – Allergy & Vegan Scan, The Gluten Free Scanner, and Eat Smart Kiwi: Food Diary. The respondents used these apps for a period of two weeks. Next, the researchers completed the MARS questionnaire, comprising five sections. The apps were evaluated in the categories of engagement, functionality, aesthetics, information content, and subjective quality assessment. Results: The study revealed that one of the apps, namely Soosee – Allergy & Vegan Scan, received the highest ratings among the apps evaluated, surpassing Eat Smart Kiwi: Food Diary and The Gluten Free Scanner, which received the lowest rating. Analysis of user preferences indicated that the aesthetics of the interface play a crucial role in the perception of mHealth mobile apps, particularly those related to food allergies. An attractive graphical interface significantly impacts user satisfaction and engagement. Notably, the ratings given by the study participants did not align with those seen on Google Play and the AppStore, suggesting potential differences in user expectations and needs depending on usage context and the more detailed assessment conducted in this study. Implications and recommendations: With numerous mobile apps available, quality assessment is crucial as users often lack the knowledge to evaluate them effectively. While mHealth apps have the potential to improve daily life for individuals with allergies, they must offer an intuitive design, verified information, and user-friendly interfaces to meet expectations. Originality/value: This study provides a comprehensive evaluation of allergy-related mobile apps using a standardized assessment tool (MARS), offering a more structured analysis than general user ratings. By highlighting discrepancies between expert-based evaluations and user reviews, the research underscores the need for more transparent quality indicators in mHealth applications.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2024, Nr 40, s. 86-97
Keywords: mobile apps; food allergies; MARS (mobile apps); m-health; aplikacje mobilne; MARS (aplikacja mobilna)